PENDUGAAN CADANGAN BIOMASSA DI ATAS PERMUKAAN TANAH PERKEBUNAN KELAPA SAWIT DI SUMATERA UTARA - Muhdi Muhdi; Iwan Risnasari; Eva Sartini Bayu (Bumi Lestari Journal of Environment, 2015)
The objective of the research was to find the model of above ground biomass in the oil palmplantation, North Sumatera. The research was done at the oil palm plantation, North Sumatera. Theeffect of oil palm plantation to biomass stock in the plots were studied by using the data ofthree plots with each size 100 m x 100 m. The plots are placed based on purposive sampling.Above ground biomass stocks are counted by allometric equation. The results of the researchshowed that allometric equation of oil palm trees was W = 0,003 D. The result  showed thatabove ground biomass of oil palm plantation in the North Sumatera were 64.20 Mg ha